Recuperação de dados da operacionalização de programas governamentais: um estudo do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) - Moreira, Fábio Mosso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Research that assess the contributions of Information and Communication Technologies (ICT) for agriculture are recent, both in the issues of use of devices by farmers as in the technological issue of dissemination of information in rural areas. The use of Internet and Web in process that provide government information is growing and brings the possibility for the citizens to monitor actions such as the implementation of public policies. Public policies for agriculture are a major factor in social and economic development of family farming. The importance to provide data about government programs and the need for farmers obtain information about public policies highlights the aims of this study, which is the analysis of data recovery process in the operacionalization of Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) through official websites of public financial institutions involved in implementing of the program. The choice by PRONAF was due to the fact that this is the main program of support for family farming in Brazil, with the largest amount of budgeted financial resources. The methodology used was a qualitative research, being essentially an exploratory-descriptive study, in which was realized a theoretical survey to obtain information to characterize the family farm, conceptualize the theme of public policy, describe the PRONAF and its operating arrangement, and to obtain factors involved in the provision and access to government data on the Web. The colect of data was performed using the method of direct observation on the official websites of public financial institutions to identify information resources containing data queries of the operationalization of PRONAF.The process of data retrieval through the informational resources identified was analyzed having with basis the aims which permeates Data Lifecycle (Preservation, Dissemination,Copyright, Quality, Integration and Privacy). The definition of criteria...

As pesquisas que abordam as contribuições das Tecnologias da Informação e Comunicação (TIC) para a área agrícola são recentes, tanto nas questões do uso dos dispositivos por parte dos produtores rurais quanto na questão tecnológica de disseminação de informações no meio rural. O uso da Internet e da Web no processo de disponibilização de informações governamentais é crescente e traz a possibilidade para o cidadão de acompanhar ações como a execução das políticas públicas. As políticas públicas para a agricultura constituem fator preponderante no desenvolvimento social e econômico da Agricultura Familiar. A importância da disponibilização de dados sobre os programas governamentais e a necessidade de agricultores familiares na obtenção de informações sobre as políticas públicas justificam o objetivo deste estudo, que consiste na análise do processo de recuperação de dados da operacionalização do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) por meio de sítios oficiais das instituições financeiras públicas envolvidas na execução do programa. A opção pelo PRONAF deve-se ao fato deste ser o principal programa de apoio à agricultura familiar no Brasil, com o maior montante de recursos financeiros orçados. A metodologia utilizada foi baseada em pesquisa qualitativa, sendo essencialmente um estudo exploratório-descritivo, na qual realizou-se um levantamento teórico a fim de obter informações para caracterizar a agricultura familiar, conceituar o tema políticas públicas, descrever o PRONAF e seu arranjo operacional, e levantar fatores envolvidos na disponibilização e acesso a dados governamentais na Web. A coleta de dados foi realizada por meio do método de observação direta nos portais oficiais de instituições financeiras públicas, a fim de identificar recursos informacionais contendo consultas aos dados da operacionalização do PRONAF. O processo de recuperação...
Keywords: Programa Nacional de Fortalecimento da Agricultura Familiar (Brasil); Agricultura familiar; Tecnologia da informação; Recuperação de dados (Computação); Family farms